New Perspectives of Residents’ Perceptions in a Mature Seaside Destination - Balbuena-Vázquez, Antonia; Hidalgo, M. Carmen; Almeida-García, Fernando; Cortés-Macías, Rafael (MPDI, 2020)
This research examines the relationship between residents of a mature tourist destination and tourism. To do this, the place attachment and rootedness shown by the residents towards the place where they live are assessed, as are their attitudes and level of satisfaction towards tourism. To carry out the research, 770 surveys were completed in the city of Benalmádena (Costa del Sol, Spain). Unlike other previous studies on place attachment, the level of place attachment and rootedness are assessed separately, using a specific indicator for rootedness. The results show that place attachment and rootedness behave differently in relation to the attitude towards tourism. Another significant result is that residents’ attitudes towards tourism in this destination are positive, being more favourable among native residents. Finally, residents show a clear level of place attachment and satisfaction with tourism development, which seems to be related to remarkable social resilience. Despite the strong vulnerability of the mass tourism model, Benalmádena displays significant resilience due to its social structure.
Keywords: Turismo; Costa del sol; Costa del Sol; Benalmádena; Place attachment; Rootedness; Attitudes towards tourism; Satisfaction; Mature destination; Social resilience